2023
DOI: 10.3390/jof9020276
|View full text |Cite
|
Sign up to set email alerts
|

Global Analyses of Multi-Locus Sequence Typing Data Reveal Geographic Differentiation, Hybridization, and Recombination in the Cryptococcus gattii Species Complex

Abstract: Cryptococcus gattii species complex (CGSC) is a basidiomycete haploid yeast and globally distributed mammalian pathogen. CGSC is comprised of six distinct lineages (VGI, VGII, VGIII, VGIV, VGV, and VGVI); however, the geographical distribution and population structure of these lineages is incompletely described. In this study, we analyze published multi-locus sequence data at seven loci for 566 previously recorded sequence types (STs) encompassing four distinct lineages (VGI, VGII, VGIII, and VGIV) within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 102 publications
1
4
0
Order By: Relevance
“…Similar results have been reported for others citrus fungal pathogens like Diaporthe citri [58] and P. citriasiana [24]. Although sexual spores are often considered as the primary source of dispersal and infections [56,59], clonal expansion of specific genotypes has been reported in many pathogens, leading to serious disease epidemics [53,[60][61][62][63][64]. Examples of clonal expansion in fungal pathogens include the banana wilt, caused by Foc TR4 that has been reported across various regions in at least 17 countries in the world [53,61,62].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results have been reported for others citrus fungal pathogens like Diaporthe citri [58] and P. citriasiana [24]. Although sexual spores are often considered as the primary source of dispersal and infections [56,59], clonal expansion of specific genotypes has been reported in many pathogens, leading to serious disease epidemics [53,[60][61][62][63][64]. Examples of clonal expansion in fungal pathogens include the banana wilt, caused by Foc TR4 that has been reported across various regions in at least 17 countries in the world [53,61,62].…”
Section: Discussionsupporting
confidence: 80%
“…The most commercially harmful Phyllosticta disease to the citrus industry in China is black spot caused by P. citricarpa and P. paracitricarpa. Our results suggest that targeted markers should be developed to monitor the prevalence and spread of clonal genotypes in these species [53,64]. In addition, the highly prevalent genotypes should be further evaluated for their susceptibilities to fungicides and for their genomic features [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…The patterns suggest the presence of unique and indigenous genetic diversity within Qatar, and that sexual mating and recombination among strains from divergent genetic clusters is not common. The presence of divergent lineages within the same geographical regions have been reported for several human fungal pathogens, including C. auris [86] and the human pathogenic Cryptococcus species complexes [89, 90]. In addition, the presence of divergent strains and clusters in both the Qatar and the global samples suggests historical genetic differentiations among subpopulations of C. glabrata .…”
Section: Discussionmentioning
confidence: 87%
“…Evidence for both recent short- and long-distance dispersals has been reported for C. glabrata and several other human fungal pathogens, including Aspergillus fumigatus [84, 85] , Candida auris [86], Candida albicans [87], Candida tropicalis [88] and multiple lineages within the human pathogenic Cryptococcus , including in both the Cryptococcus neoformans and Cryptococcus gattii species complexes [89, 90]. However, in most of these molecular epidemiological and population genetic studies of human fungal pathogens, few isolates were from the Middle East region, an ecologically distinct region with a hot climate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that free-living microbial eukaryotes smaller than 1–3 µM are highly mobile and can be effectively dispersed by wind over long distances; thus, blurring the potential effects of geographic separation on their genetic relationships ( 12 , 13 ). Though spores (e.g., asexual spores, ascospores, and basidiospores) of many fungi are in that size range and found cosmopolitan, an increasing number of fungal species showed significant contributions of geography, topography, climate oscillations, ecological, and physical barriers to their genetic variation, such as in Aspergillus ( 9 , 14 ), Cryptococcus ( 15 , 16 ), Neurospora ( 17 , 18 ), yeast ( 19 , 20 ), etc. In A. fumigatus , the effects on prominent local and regional landscape factors, such as steep mountains and deep gorges to genetic variations remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%